Anti-platelet therapy: phosphodiesterase inhibitors - Gresele, Paolo (Blackwell Science Inc, 2011)
Inhibition of platelet aggregation can be achieved either by the blockade of membrane receptors or by interaction with intracellular signalling pathways. Cyclic adenosine 3′,5′-monophosphate (cAMP) and cyclic guanosine 3′,5′-monophosphate (cGMP) are two critical intracellular second messengers provided with strong inhibitory activity on fundamental platelet functions. Phosphodiesterases (PDEs), by catalysing the hydrolysis of cAMP and cGMP, limit the intracellular levels of cyclic nucleotides, thus regulating platelet function. The inhibition of PDEs may therefore exert a strong platelet inhibitory effect. Platelets possess three PDE isoforms (PDE2, PDE3 and PDE5), with different selectivity for cAMP and cGMP. Several nonselective or isoenzyme-selective PDE inhibitors have been developed, and some of them have entered clinical use as antiplatelet agents. This review focuses on the effect of PDE2, PDE3 and PDE5 inhibitors on platelet function and on the evidence for an antithrombotic action of some of them, and in particular of dipyridamole and cilostazol.